Can China’s ocean governance system improve the marine ecosystem? – Taking the “bay chief system” as an example - Chen, Yusheng; Zhou, Yongwei; Ma, Ye; Sun, Zhaofa; Yang, Weili (Frontiers in Marine Science, 2024)
Marine ecosystem governance is an important component of the goal of developing a strong maritime nation, as well as an urgent need to ensure national maritime security. The "Bay Chief System"(BCS) is a novel policy concept with Chinese roots that seeks to improve the marine ecological environment. In this paper, we take the coastal cities in China as an example and use the panel data of prefecture-level cities from 2010 to 2022 to analyze the impact of the Bay Chief System on the regional marine ecological environment by using a differences in-differences model. The baseline regression results reveal that the implementation of the Bay Chief System leads to a 0.122 percentage point improvement in marine ecosystems but it has yet to be linked to the River Chief System(RCS) to establish a systematic synergistic mechanism. Heterogeneity analysis reveals that the implementation of the Bay Chief System is more effective in coastal cities with smaller populations, a heavier proportion of secondary industries, and a geographic location closer to the South. The analysis of the impact mechanism indicates that the Bay Chief System mitigates the adverse effects of near-shore resource development on the marine ecological environment by regulating the intensity of fishery and coastal tourism development. Additionally, it optimizes water quality by substantially reducing pollutants like chemical oxygen demand (COD) and ammonia nitrogen (AN) in seawater, ultimately contributing to the protection of the marine ecological environment.Keywords: Bay Chief system; marine ecosystem; Differences-in-Differences construction of a modern socialist country -Report on the 20th National Congress of the Communist Party of China (CPC) -Seekingalpha.com(